Baxter’s Nerve Entrapment: The Missing Nerve - Shivani Choudhary; Abhinav Sathe; D. Vijay Kumar (Archives of Medicine and Health Sciences)
Baxter’s neuropathy is a rare condition that has often been overlooked in the realm of peripheral nerve disorders. This brief communication aims to shed light on the elusive nature of Baxter’s neuropathy, emphasizing the significance of recognizing and understanding this condition for proper diagnosis and management. By addressing this “missing nerve,” we hope to contribute to improved patient outcomes and enhance the overall understanding of peripheral nerve pathologies.